Studies on lysine utilisation and dietary lysine requirement with Atlantic salmon (Salmo salar L.) parr - Hauler, Rhys(Rhys Carlile) (2002)
For Atlantic salmon, estimates of the efficiency of lysine utilisation for growth (liveweight, protein and lysine gain) and obligatory loss (maintenance) are currently unavailable. The primary aim of this thesis was to examine efficiency of lysine utilisation in Atlantic salmon parr under various nutritional constraints. Where possible, results were discussed in a comparative perspective to identify the similarities between fish and terrestrial animals. Lysine utilisation by parr was used to evaluate a factorial approach to determine the lysine requirement (allowance), which remains relative unexplored in fish nutrition. When Atlantic salmon parr were fed lysine intakes that limited growth response (marginal lysine intakes) the efficiency of lysine utilisation for lysine gain was 0.71. A similar efficiency was confirmed for marginal lysine intakes in published lysine requirement studies for Atlantic salmon. Based on these observations, reevaluation of published dietary lysine requirements of fish identified a constant efficiency of utilisation for liveweight gain (54.1 mg liveweight gain.mg-1 lysine intake). Consequently, the lysine requirements of different fish species were shown to be similar when expressed relative to liveweight gain (18.5 g liveweight gain). Further studies with Atlantic salmon parr investigated the influence of feeding regime, daily nutrient intake and dietary protein level on the efficiency of lysine utilisation. Under satiation or controlled (% BW.d-I ) feeding, the efficiency of lysine utilisation for lysine gain was 0.67 and 0.71, respectively. Fed at daily nutrient intakes of either 3.92 g DP (digestible protein).kg-1 BW.d-I and 154.6 kJ DE (digestible energy).kg -I BW.c1-1 or 3.47 g DP.kg BW.d-1 and 175.1 kJ DE.kg - 1 BW.c1-1 , the efficiency of lysine utilisation for lysine gain was 0.77 and 0.71, respectively. Collectively, these studies demonstrated that under adequate nutrition the efficiency of lysine utilisation parr remained within a narrow range and similar to terrestrial ...